Micellization and gelatinization in aqueous media of pH- and thermo-responsive amphiphilic ABC (PMMA82-b-PDMAEMA150-b-PNIPAM65) triblock copolymer synthesized by consecutive RAFT polymerization - Ye Huang (2017)
The multi-stimuli-responsive amphiphilic ABC triblock copolymer of poly(methyl methacrylate)-block-poly[N,N-(dimethylamino) ethyl methacrylate]-block-poly(N-isopropylacrylamide) (PMMA-b-PDMAEMA-b-PNIPAM) was synthesized by sequential reversible additionâ fragmentation chain transfer (RAFT) polymerizations. Due to the pH- and thermo-responsive blocks of PDMAEMA and thermo-responsive blocks of PNIPAM, the copolymer solution properties can be manipulated by changing the parameters such as temperature and pH, and it formed diverse nanostructures and had gel behavior in different conditions. In detail, when the pH was below 7.3, the pKaÂ of DMAEMA, tertiary amino groups were protonated, the polymer micellar solution like weak gel changed into free-standing gel at around 40 Â°C even at a low concentration of 2 wt%. Further, the gel behavior and morphology of the system were studied by rheology, turbidimetry measurements, transmission electron microscopy (TEM) and scanning electron microscopy (SEM), respectively. When the pH was above the pKa, the triblock copolymer self-assembled into diverse micellar structures including shellâ core, coronaâ shellâ core and shellâ shellâ core nanoparticles as the temperature increased, but no free-standing gelation. The two-step thermo-responsive behavior, corresponding to the different LCSTs of PNIPAM block and DMAEMA block, was evidenced by turbidity analysis. The assembled structures rapidly collapsed due to the enhanced hydrophobic interaction when the temperature further increased. Dynamic light scattering (DLS) was used to confirm the transitions.